JUNGIAN INDIVIDUATION IN RED DEAD REDEMPTION 2: ARCHETYPAL ANALYSIS OF ARTHUR MORGAN'S MORAL TRANSFORMATION - Al Ayyubi, Mohammad Taaba (Universitas Negeri Surabaya, 2026)
This study analyzes Red Dead Redemption 2 as a modern literary work by examining archetypes and symbolic themes in one of its most emotionally impactful scenes, commonly referred to by players as the